The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1093/aje/kwx267
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentrations of Persistent Organic Pollutants and Unhealthy Metabolic Phenotypes in Normal-Weight, Overweight, and Obese Individuals

Abstract: Factors underlying metabolic phenotypes, such as the metabolically healthy but obese phenotype, remain unclear. Differences in metabolic phenotypes-particularly, among individuals with a similar body mass index-could be related to concentrations of persistent organic pollutants (POPs). To our knowledge, no studies have analyzed POPs and metabolic phenotypes in normal-weight persons. We investigated the relationships between serum concentrations of POPs and metabolic phenotypes in 860 normal-weight, overweight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The Anniston community survey showed a positive association between serum PCB levels and self-referred diabetes prevalence, but the association was found in females only and was imprecise in older people, who however had the highest PCB serum levels (Silverstone et al., 2012). PCB serum concentration was positively associated with diabetes, prediabetes and unhealthy metabolic pattern also in a cross-sectional study in a Spanish general population, with a stronger association in normal-weight than overweight-obese subjects (Gasull et al., 2012, 2017). In another cross-sectional study in a Native American population, however, an association was found between diabetes and only low-chlorinated PCB congeners, which are the most volatile congeners, suggesting that the main route of exposure was inhalation (Aminov et al., 2016).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The Anniston community survey showed a positive association between serum PCB levels and self-referred diabetes prevalence, but the association was found in females only and was imprecise in older people, who however had the highest PCB serum levels (Silverstone et al., 2012). PCB serum concentration was positively associated with diabetes, prediabetes and unhealthy metabolic pattern also in a cross-sectional study in a Spanish general population, with a stronger association in normal-weight than overweight-obese subjects (Gasull et al., 2012, 2017). In another cross-sectional study in a Native American population, however, an association was found between diabetes and only low-chlorinated PCB congeners, which are the most volatile congeners, suggesting that the main route of exposure was inhalation (Aminov et al., 2016).…”
Section: Discussionmentioning
confidence: 74%
“…PCBs have been classified as endocrine disruptors because they can interact with several functions of endocrine system, particularly the thyroid and reproductive organs (El Majidi et al., 2014). Various studies have also found that PCBs are associated with diabetes, insulin resistance and unhealthy metabolic phonotype (Kuo et al., 2013; Taylor et al., 2013; Gasull et al., 2017), and cardiovascular diseases, particularly hypertension (Everett et al., 2008, 2011). However, current evidence on the role of PCBs as determinants of endocrine, metabolic or cardiovascular disease is still inconclusive (Warner et al., 2013; Lee et al., 2014; Henríquez-Hernández et al., 2017; Benson et al., 2018), Brescia is a highly industrialized town in North Italy where a chemical factory produced PCBs from 1938 to 1984 (CTS , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These observations argue against the need to condition on total lipids, BMI or smoking. 16 , 21 Nevertheless, to explore alternative scenarios, in some instances we also used lipid-corrected POPs or further conditioned on BMI or smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas matching factors included age, date and time of the day of blood collection, and fasting status, results are coherent with the notion that exposure misclassification is lower and the comparison of POP measures between cases and controls more accurate among participants who fast longer or have normal weight. 1 , 9 , 13 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation